Crack growth in Fe–2.7 wt% Si single crystals under cyclic loading and 3D atomistic results in bcc iron. (June 2016) - Landa, Michal; Machová, Anna; Uhnáková, Alena; Pokluda, Jaroslav; Lejček, Pavel
Graphical abstract: Crack deflection after cycling in mode I with P max = 2.5 kN and stress ratio R = 0. Highlights: Crack growth in Fe–Si crystals loaded cyclically in mode I at 300 K is presented. Experiments on Fe–Si are compared with observations by molecular dynamics (MD). 3D atomistic results help to understand fatigue crack growth in experiments. MD and experimental results can be described by close Paris exponents. Abstract: To search for correlations between experiments on macro-level and atomistic results on nano-scale, new experimental results from fracture tests under cyclic loading performed at room temperature on bcc iron-silicon single crystals with edge crack ( 1 ¯ 1 0 ) [1 1 0] (crack plane/crack front) are presented. The crystals were loaded in mode I with stress ratio R = 0. Crack growth Δ a under various values of the applied stress intensity Δ KA and acoustic emission response were monitored simultaneously. Experimental results comply with the basic predictions on fatigue crack growth following from continuum modeling and with molecular dynamic (MD) simulations in bcc iron. MD and experimental results can be described by very similar values of the Paris exponents although different length scales are treated in the two methods.